(untitled) (Al-Mansour Journal, 2022)
Transferred rights collecting contract is a contract concluded by the creditor when he transfers his right to another person, and is known as the "factor", which conforms to guarantee the payment in case the debtor has failed to pay the debt to the creditor. The paper deals with examining the most important problem,which is the obsence of acertain legal system to such an issue since the Iraqi legislator did not deal with such system, aiming at solving this problem, as well as displaying a solution for the problem of the law supposed to be applied in relation to settling any conflict which might arise between its parties after getting to its legal adjustment. We followed the comparative and analytical style in writing this paper. We have concluded that this contract is considered one of the unnamed contracts in the Iraqi law, and it has a certain quality. It is a legal system combined of some legal rules derived from certain legal aspects like right transfer and fulfillment of subrogation. Some of our most important recommendations to the Iraqi legislator is finding a suitable way to activate the factoring system in Iraq, constructing specialized companies for this purpose, in addition to regulating it in a certain law which might achieve legal security to the national investor who needs to get rid of the fear element when concluding a contract with a foreign party.